Aspects of the Binding of Acyclic Carotenoids to Flabelliferins from Palmyrah Fruit Pulp - Uluwaduge, I.; Jayaweera, P.M.; Ileperuma, N.; Jansz, E.R.; Thabrew, M.I. (My University, 2009)
The fruit pulp of palmyrah (Borassus flabellifer) contains flabelliferins which are glycosides of p-sitosterol. Naturally bound to flabelliferins is an UV active compound, phytofluene, which affects biological activity. This UV active compound shows intense blue fluorescence and can be dissociated from flabelliferins. The objectives of this study were to determine the main carotenoid binder to flabelliferin- II (F-II, a tetraglycoside) in a sample of PFP from Kalpitiya,Sri Lanka by HPLC and some of the chemical features of this complex (F-II+ carotenoid binder). HPLC studies showed that the major binder to F-II in a sample ofPFP from Kalpitiya was phytofluene. No correlation was found between the stoichiometry of binding of phytofluene and F-Il (r2= 0.406) as well as for Fb (r2=0.007) indicating that the binding ratios of phytofluene with F-UJ()r Fb are not constant in different PFP samples tested. Computational calculations (-~~Hf /KJ mol") suggest that binding is a less stable between F-II and phytofluene compared to the other flabelliferins tested. This was probably due to phytofluene distorting the conformation of the carbohydrate moiety of F-II. Computer modeling provided confirmatory evidence for this assumption.
Keywords: Palmyrah; Borassus flabelifer; Flabellirerins